A rare case of pulmonary thromboembolism with lobar pneumonia in a factor 7 deficiency patient - Thalari, Hari Kiran; Bhattacharya, Meenakshi; Gupta, Ishank; Jadhav, Punam (International Journal of Research in Medical Sciences, 2024)
While thrombotic events are uncommon in individuals with Factor VII deficiency, they have been documented, particularly when other prothrombotic risk factors are present, such as recent surgical interventions, trauma, or factor replacement therapy. This case report discusses a 45-year-old male with a known history of Factor VII deficiency who initially presented with symptoms of fever and productive cough, leading to a diagnosis of lobar pneumonia based on clinical examination and chest X-ray results. However, after four days of hospitalization, the patient exhibited persistent coughing, occasional hemoptysis, and breathlessness, raising clinical suspicion of pulmonary thromboembolism (PTE), which was later confirmed via computed tomography pulmonary angiography. Treatment with anticoagulation led to significant clinical improvement. This case illustrates that despite having Factor VII deficiency, the patient developed PTE.